1999
DOI: 10.1046/j.1365-294x.1999.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollen dispersal inferred from paternity analysis in a mixed oak stand of Quercus robur L. and Q. petraea (Matt.) Liebl.

Abstract: Paternity analysis was used to determine the spatial distribution of male parents of 984 offspring collected from 13 identified mother trees in a natural stand of 5.76 ha and comprising 296 adult trees of Quercus petraea and Q. robur. For seven of the 13 maternal progeny arrays sampled, we found an excess of nearby matings and a preferential direction of pollination. For the remaining progeny arrays, no departure from random distribution of male parents was detected. A common trend among all families was a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
361
4
12

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(423 citation statements)
references
References 26 publications
41
361
4
12
Order By: Relevance
“…These observations confirmed that a few microsatellite markers were enough for paternity assignment. As shown for some other species, the large number of low-frequency alleles and their distributions, typical of microsatellite loci, positively influence the exclusion probabilities (Dow and Ashley 1998;Streiff et al 1999;Kameyama et al 2000;Konuma et al 2000). The overall outcrossing rate was high (96.7%) with no neighbouring effect.…”
Section: Reproductive Behaviour Inside the Seed Orchardmentioning
confidence: 75%
See 3 more Smart Citations
“…These observations confirmed that a few microsatellite markers were enough for paternity assignment. As shown for some other species, the large number of low-frequency alleles and their distributions, typical of microsatellite loci, positively influence the exclusion probabilities (Dow and Ashley 1998;Streiff et al 1999;Kameyama et al 2000;Konuma et al 2000). The overall outcrossing rate was high (96.7%) with no neighbouring effect.…”
Section: Reproductive Behaviour Inside the Seed Orchardmentioning
confidence: 75%
“…Microsatellite data were used in the paternity analysis, using FaMoz software (S. Gerber, unpublished), which assigns paternity to a particular pollen donor, based on the likelihood-ratio method. The paternity assignment methods by exclusion procedures were detailed in Streiff et al (1999) and Gerber et al (2000). The multilocus genotype of the mothers and 349 potential fathers was known for each offspring.…”
Section: Paternity Assignmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A common observation is that a few tens percent of acorns result from pollination with immigrating pollen (e.g. Streiff et al 1999;Curtu et al 2009;Lepais and Gerber 2011;Buschbom et al 2011), and the immigration rate is relatively stable at the stage of established seedlings (Chybicki and Burczyk 2010;Lepais and Gerber 2011). This suggests that the population of Q. pubescens in Bielinek should experience a permanent oak pollen flow from the outside as well.…”
Section: Introductionmentioning
confidence: 99%